Seismic resistance evaluation of reinforced concrete (RC) exterior beam-column joints with and without GFRP under quasi-static lateral cyclic loading by adopting experimental analysis - Mohd Razmi Mohd Amit,; Asma Nabila Abd. Kader,; M.Y.M Yatim, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The beam-column joint is an important component of Reinforced Concrete (RC) structures because its design and detailing are critical to the safety of these structures under seismic loading. In recent decades, structural behaviour of beam-column joints has been widely explored. To better understand the behaviour of beam-column joints, researchers have conducted experiments and provided analytical and experimental solutions. The seismic behaviour of beam-column joints with and without Glass Fibre Reinforced Polymer (GFRP) when subjected to quasi-static lateral cyclic loading was compared in this research using two specimens. The first specimen is a typical RC exterior beam-column joint without GFRP while the second specimen is RC exterior beam-column joint that is pre-installed with Glass Fibre Reinforced Polymer (GFRP) using Near-Surface Mounted (NSM) technique. The specimens were evaluated to a drift of 2.0% under quasi-static lateral cyclic loading. There were two cycles in each drift. Based on the amplitudes of both specimens, it can be seen that the amplitude of beam-column joint with GFRP is lower than the beam-column joint without GFRP. This suggests that the presence of GFRP reduces the intensity of the loading. This study also discusses the energy dissipation and equivalent viscous damping on both specimens. During the experiment, each crack, void between the concrete, and spalling of concrete fragments were carefully monitored. Visual observation during the experiment shows that severe cracking is evident on the inner part of the structure in both specimens. Therefore, a new location of GFRP-NSM would be suggested for a future experiment.